Megadose Vitamin C Prescription Through Alternative Medicine Leading to End-Stage Renal Disease: Case Study and Literature Review - Sasmit Roy MD; Prabal Chourasia MD; Vikram Sangani MD; Praveen Kumar Errabelli MD; Sumit S. Patel MD; Sreedhar Adapa MD (SAGE Publishing, 2023)
Modern medicine has made tremendous advancements and succeeded in increasing longevity through adequate screening and diagnosis and various new therapeutic approaches. However, alternative medicine is a branch of health care practicing different traditional and unconventional, potentially hazardous therapies to treat commonly known ailments. Standard low-dose vitamin C, ie, 500-1000 mg, is approved in medical conditions like methemoglobinemia, scurvy, burns and also helps iron absorption in anemia. However, toxic doses carry high nephrotoxicity potential like in our case. We present a 74-year-old Caucasian female falling victim to one such alternative therapy leading to acute kidney injury requiring lifelong hemodialysis. She had endometrial cancer and received 100 gm of intravenous vitamin C weekly through a provider for the last 6 weeks as part of this alternate approach to cure her cancer. Upon admission, the serum creatinine level was elevated at 8.2 mg/dl, which subsequently did not improve with conservative management. Renal biopsy revealed diffuse acute tubular injury with polarized microscopy demonstrating calcium oxalate crystals. While her blood vitamin C levels were high, the serum oxalate level was normal. She ended up requiring renal replacement therapy permanently. Alternative medicine continues to be a significant health care hazard with the potential to cause unwanted irreversible nephrotoxicity. Public attention is necessary at various social levels to counter the detrimental outcomes of alternative medicine.